Distributed Data Processing in Vehicular Networks using Mobile Agents - Urra, Óscar; Ilarri, Sergio (Jornada de Jóvenes Investigadores del I3A, 2017)
In a vehicular network, vehicles can exchange interesting information (e.g., about accidents, traffic status, etc.) using short-range wireless communications. Besides, the vehicles can be equipped with additional sensors that can directly obtain data from the environment. How to efficiently process and collect these data is an open problem. We argue that mobile agent technology could be helpful.